RESULTS OF STATE PROGRAM OF ACTION STRATEGY - INCREASING HUMAN BENEFITS AND EDUCATIONAL EFFICIENCY - Kimsanboev Rakhmonjon Valizoda, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In this article, the Decree of the President of the Republic of Uzbekistan dated February 7, 2017 "On the Strategy of Actions for the Further Development of the Republic of Uzbekistan" on the implementation of the Strategy of Actions in the "Year of Communication with the People and Human Interests" in the 4th direction of the State program [1] called "Development of the social sphere", measures to ensure the convenience of preschool educational institutions, improve the quality of general secondary, secondary special and higher education and their development will be explained in detail. In this direction, the results of the special attention paid to the development of the field of education and science, to the education of well-rounded, intellectually mature, and at the same time, highly qualified specialists are analyzed.